The Relationship of Anxiety with Basic Shooting Techniques Skills of Beginner Athletes Women's Soccer - Allifa Dwi Apri; Tite Juliantine; Nuryadi (Journal of Physical Education Health and Sport, 2026)
This research is motivated by the importance of psychological aspects in football, especially the anxiety that novice athletes often experience when facing match situations. Uncontrolled levels of anxiety can affect a player's concentration, decision-making, as well as basic technical skills, especially in shoting, which is an important ability to score goals. Therefore, this study aims to determine the relationship between anxiety level and basic shoting technique skills in novice female football athletes at Goal Aksis Football School. The research uses a quantitative method with a correlational descriptive design. The study subjects consisted of 18 15-year-old female football novice athletes who were selected using purposive sampling techniques. Data collection was carried out through a Sport Competition Anxiety Test (SCAT) questionnaire which was modified into 20 statements to measure anxiety, an anxiety observation sheet based on physiological, psychological, and behavioral indicators, and a shoting skill test using the Bobby Charlton method to measure shot accuracy. Data analysis was carried out using descriptive statistics, normality test, Pearson correlation test and determination coefficient (R Square) with a significance level of 0.05. The results showed that the data were normally distributed and there was a very strong relationship between anxiety and basic shoting technique skills, with a correlation coefficient value of r = 0.998 and a significance value of p < 0.05. The determination coefficient of 0.996 showed that 99.6% of the variation in shoting ability was influenced by the athlete's anxiety level. Based on these results, it can be concluded that anxiety has a very significant relationship with the basic shoting technique skills of novice female football athletes, so the management of mental aspects needs to be considered in the process of coaching and training athletes.